Relation between the mineral nutrients and the Vitamin C content in camu-camu plants (Myrciria dubia) cultivated on high soils and flood soils of Ucayali, Peru (Scientia Agropecuaria, 2016)
Camu-camu is a native plant of the Peruvian Amazon. It is noted for its high concentration of ascorbic acid, however this feature varies widely from one location to another due to genetic and environmental factors. In order to determine the relationship between mineral nutrients and the concentration of ascorbic acid in camu-camu plants, a study was conducted in three camu-camu producing areas in flood-prone soils and soils on dry land conditions in the Ucayali Region. For this purpose, soil samples and camu-camu were collected. The content of following macronutrients was analyzed: nitrogen, phosphorus, potassium, calcium and magnesium; also was determined the concentration of aluminum, pH, organic matter and ascorbic acid. The results show that the camu-camu plantations located in upland soils had lower concentrations of ascorbic acid and lower natural fertility, than soils prone to flooding. Ascorbic acid is negatively related to the concentration of aluminum and positively to the concentration of magnesium and phosphorus in the camu-camu producing areas. It is concluded that the concentration of ascorbic acid in camu-camu plants is best expressed when soils have better chemical attributes and good conditions of natural fertility.